Anti-inflammatory Terpenes from Flowers of Inula japonica - Tang, Sheng-An; Zhu, Hong; Qin, Nan; Zhou, Jing-Ya; Lee, Eunkyung; Kong, De-Xin; Jin, Mei-Hua; Duan, Hong-Quan (Planta Medica, 2014)
Five new terpenes (1–5) and ten known compounds (6–15) were isolated from Inula japonica, and their structures were identified by spectroscopic analysis. Compounds 3 and 14 showed positive inhibitory effects on nitric oxide production. Furthermore, compound 14 suppressed both leukotriene C4 synthesis and degranulation in c-kit ligand-induced bone marrow-derived mast cells.
Keywords: Inula japonica; Compositae; terpene; anti-inflammatory; NO; LTC4; degranulation